The Role of Capital Expenditure in Mediating the Influence of Local Revenue on Local Financial Performance (A Study of Regency/City Governments in Bali Province) - Jesika, Komang Lerin; Purnawati, Ni Ketut (CV. Lenggogeni Data Publishing, 2025)
Regional financial performance is a reflection of the level of achievement or financial condition that can reflect the ability of regional governments to manage and utilize financial resources. Regional financial performance is measured using the independence ratio. Regional original income is all regional revenue derived from the management of the region's own economic resources. Capital expenditure can reflect that government revenue can be seen from the development of infrastructure and facilities needed by the region. This study aims to determine the effect of local revenue on capital expenditure as a mediator. The type of data used in this study is secondary data obtained from the official websites of the Central Statistics Agency and the Directorate General of Fiscal Balance. The population in this study is all regencies/cities in Bali Province for the period 2018-2023, namely 9 regencies/cities. The sampling method used in this study was a census method with saturated sampling technique, which used the entire population as the research sample, resulting in a total of 54 samples over a period of 6 years. The analysis technique used was path analysis. Based on the test results, it was found that local revenue had a positive and significant effect on local capital expenditure, local revenue had a positive and significant effect on local financial performance, capital expenditure had no effect on local financial performance, and capital expenditure was unable to mediate the effect of local revenue on local financial performance.